METHODOLOGY FOR DEVELOPING COGNITIVE INDEPENDENCE IN EXTRACURRICULAR ACTIVITIES BASED ON ARTIFICIAL INTELLIGENCE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article analyzes the issue of developing students’ cognitive independence through the use of artificial intelligence technologies. The didactic possibilities of digital technologies, particularly AI-based educational tools in extracurricular activities, are examined. In addition, the methodology for forming students’ independent thinking, analytical skills, and creative approaches is discussed.